Spatial-temporal Evolution Rule Analysis of Runoff of Hanjiang River under Changing Environment - ZHONG Huayu; HUANG Qiang; YANG Yuanyuan; LIU Dengfeng; MING Bo; REN Kang (Renmin Zhujiang)
Runoff series is the basic data for the planning, design and operation management inhydraulic engineering. As the largest tributary of the Yangtze River, the Hanjiang River is thewater source area of middle route of the South-to-North Water Diversion Project and Hanjiang-to-Weihe River Water Diversion Project in Shaanxi province. Therefore, it has great significance tostudy the runoff evolution rule in Hanjiang River Basin for ensuring the water resources securityand improving the carrying capacity of regional water resources. Based on the 48-year measureddaily runoff series of the hydrological stations of Yangxian, Huangjiagang and Huangzhuang in themain stream of the Hanjiang River, this paper comprehensively analyzes the spatial-temporalevolution trend, year of abrupt change, periodic variation, interannual variation and annualdistribution of runoff in Hanjiang River Basin via multi methods and multi dimensions. The resultsshow that the runoff consistency was broken as follows: ① The annual runoff from the upper,middle and lower reaches of the Hanjiang River decreased with the trend of -312 million m3/(10a),-1 478 million m3/(10a) and -593 million m3/(10a) respectively, and the downward trend continuedstrongly, but the monthly runoff of lower reaches of the Hanjang River was increased significantlyin January and February; ② The abrupt change of the Hanjiang River occurred in 1985 and 1990, andthe inter-annual variation characteristic values and the annual distribution characteristicindexes of these stations decreased slightly after the abrupt change; ③ The runoff series of theHanjiang River had three types of periodic changes: 40~48 a, 11a and 4~7 a; ④ The inter-annualrunoff variation coefficient of the Hanjiang River was between 0.28 and 0.46, and the extremeratio was between 2.72 and 7.73; ⑤ The maximum monthly average runoff of the three stations wasin July or September, and the minimum monthly average runoff was in December or February, and theannual distribution of runoff was concentrated in July to October, accounting for more than 50% ofthe annual runoff. This study has guiding significance for the future planning, design, operationmanagement, and water resources allocation of hydraulic engineering in the Hanjiang River Basin.At the same time, it can provide a research idea for analyzing the spatial-temporal evolution ruleof runoff in other river basins.